Selected Methods of Therapeutic Interactions With People With Mild Symptoms of Autism Spectrum Disorder - Marta, Kopańska; Justyna, Chojdak-Łukasiewicz; Marta, Sochocka; Jerzy, Leszek; Justyna, Podgórska-Bednarz; Agnieszka, Banaś-Ząbczyk̨; Danuta, Ochojska (Frontiers in Psychiatry, 2022)
In this review we present the behavioral aspects of interaction in people with autism spectrum disorders (ASD), taking into account some aspects of pharmacotherapy. In the treatment of people with ASD, an individual approach to emotional, social and cognitive functioning is very important. The specificity of symptoms and their severity in people with ASD results from deficits/disfunction of various areas of the brain and is associated with different levels of intelligence. This manuscript considers selected methods of interaction with ASD patients with normal IQ. Due to the different ways of functioning, these people often find it difficult to adapt to social expectations. The most important thing is to understand their perception of themselves and the world around them in order to support them in coping with the daily challenges. Due to the increasing problem, more and more attention is being focused on early detection of ASD, what allows to intervene as fast as possible and in consequence affect the quality of life of people with this dysfunctions. However, participants with mild autism symptoms are still difficult to diagnose in the practice. The effectiveness of the therapy depends largely on the cooperation of educational institutions. It is also necessary to contact specialist clinics, including a mental health counseling center. However, in the case of children and adolescents, the cooperation between the therapist and their parents is the basis. Systemic family therapy is also important in adults with ASD. An overview of the methods of therapeutic interactions in ASD, what may be helpful in diagnosing of mild ASD, were presented in our manuscript.